Role of Clinical Pharmacist in Context of World Health Organization against COVID-19 - Khan, Majid (Journal of Pharmacy Practice and Community Medicine)
Dear Editor, Since December 2019, the outbreak of novel human virus on the name of COVID-19 spread in China from Wuhan city around the world to 183 countries in 2020.[1] This virus considered lethal for many people. Most of the people who infected get respiratory symptoms include cough, shortness of breath, sneezing and fever. The novel virus transmitted in contact person to person via droplets of cough or sneezes from infected person or animal. High risks to those peoples who are in outbreak areas or with other complications include immune-compromised patients, diabetes mellitus, cardiac diseases and any other co-morbidities.[2] Clinical Pharmacists are more easily accessible healthcare professionals to public and key figures of health care team regarding infectious diseases. According to Amir M et al. Clinical Pharmacy is the liaison of pharmacist with physician in which Clinical pharmacists prescribing medications.[3,4] Wasim et al. articulated that Clinical Pharmacists are independent prescribers in United Kingdom.[5] In current pandemic pharmacists may consider secondary prescriber due to physician’s self-illness and inpatient focuse.[1] World Health Organization being a standard organization around the world providing health to worldwide population, mandate some qualities upon the Pharmacists that a good pharmacist bears seven qualities every quality called as star thus named as “Seven stars Pharmacist” includes communicator, teacher, decision maker, leader, manager, lifelong learner, caregiver[6] additional two are researcher and pharmapreneur thus total becomes “Nine stars Pharmacist” (Figure 1), almost all of these are implemented in developed countries in outbreak of novel corona virus which was expected WHO few years ago now the time for these professionals proving their selves.